Evaluation of maximum percentage glucose conversion for dilute acid hydrolysis of kenaf biomass using statistical analysis - Mohd Nasir, Nur Aimi; Mustafa Kamalbahrin, Mohd Adlan; Seeni Mohamed, Nurhafizah; M.I, Ahmad Fitrie; Anuar, Hazleen; Mel, Maizirwan; Othman, Rashidi (Trans Tech Publications, Switzerland, 2012)
Kenaf (Hibiscus cannabinus.L) is a crop- that produces about 70% of biomass larger than any of forest plantations. There is no specific way of using kenaf biomass in industry instead for animal feed and burning in various forms (waste in general). As a result, several researches had been conducted to utilize it in the production of biodegradable polymer as well as bioethanol. This is due to its complex cellulose content that is useful to be converted into glucose before further process. The conversion step from cellulose content of kenaf biomass into glucose is known as pretreatment process. In this paper, dilute acid hydrolysis was chosen as the pre-treatment process. With the aim to evaluate the maximum percentage of glucose conversion for this kind of pretreatment process from kenaf biomass, statistical analysis which is analysis of variance (ANOVA) design via central composite design using response surface method (RSM) was selected. Thus, the lower the mass which is at 2 g, and at higher temperature which is 180 oC in longer time which is in 60 min results about 25.33% glucose conversion with the comparison of the predicted value obtained from the experimental design.